2022
DOI: 10.1186/s12871-022-01805-3
|View full text |Cite
|
Sign up to set email alerts
|

Sedative effect of remimazolam combined with alfentanil in colonoscopic polypectomy: a prospective, randomized, controlled clinical trial

Abstract: Background Remimazolam is a newer benzodiazepine with properties of rapid onset, short duration of action, and fast recovery. Our study was to evaluate the effects of different doses of remimazolam combined with alfentanil in colonoscopic polypectomy. Methods One hundred twenty patients were randomly divided into four groups: alfentanil and propofol (AP) group, alfentanil and remimazolam 0.1 mg/kg (AR1 group), 0.15 mg/kg (AR2 group), or 0.2 mg/kg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
12
0
2
Order By: Relevance
“…Previous studies confirmed that RT could be safely and effectively used for sedation in outpatient surgeries, such as gastrointestinal endoscopy (Rex et al, 2018;Lu et al, 2022;Xin et al, 2022), bronchoscopy (Pastis et al, 2019), tooth extraction (Zhao et al, 2022), hysteroscopy (Zhang et al, 2021), or induction and maintenance of general anesthesia (Zhou et al, 2020;Mao et al, 2022). RT could also provide enough sedative effect and safety for special patients, such as elderly patients (Liu et al, 2022;Tan et al, 2022) and patients with liver cirrhosis (Cao et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies confirmed that RT could be safely and effectively used for sedation in outpatient surgeries, such as gastrointestinal endoscopy (Rex et al, 2018;Lu et al, 2022;Xin et al, 2022), bronchoscopy (Pastis et al, 2019), tooth extraction (Zhao et al, 2022), hysteroscopy (Zhang et al, 2021), or induction and maintenance of general anesthesia (Zhou et al, 2020;Mao et al, 2022). RT could also provide enough sedative effect and safety for special patients, such as elderly patients (Liu et al, 2022;Tan et al, 2022) and patients with liver cirrhosis (Cao et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Alfentanil is widely used in intravenous general anesthesia. The combination of alfentanil and dexmedetomidine, ketamine or propofol has been well used in various short and minor operations [1,[20][21][22] .Previous studies on alfentanil mainly focused on the use of single bolus injection or on-demand administration of alfentanil [23] .In this study, continuous infusion can improve the quality of sedation and analgesia, rapidly adjust the depth of anesthesia, and signi cantly reduce the occurrence of hemodynamic uctuations and respiratory depression. We found that the incidence of respiratory depression in the high dose group of alfentanil increased signi cantly, indicating that when the dosage of alfentanil reached 0.35µg/kg/min, the safety of respiration decreased signi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…The current study also showed that TLOC and ADS 50 were higher in the group receiving remimazolam than those in the group receiving propofol during remifentanilbased TIVA; this result is consistent with the results of previous studies. BIS and the Modified Observer Assessment of Alertness and Sedation (MOAA/S) scores have been used in previous comparative studies on the effects of remimazolam and propofol on the depth of anesthesia (17)(18)(19)(20). However, BIS was originally developed for monitoring the depth of propofol-based anesthesia, and there is a weak correlation between benzodiazepine-induced anesthetic depth and BIS (4).…”
Section: Tloc and Anesthetic Depthmentioning
confidence: 99%